Implementation of Polynomial Regression on Coconut Charcoal Making System Integrated with IoT and Cloud in Real Time - Chairunisa, Difa; Ardhiah, Aulia; Prasetyo, Muhammad; Santoso, Iman Hedi; Budiman, Gelar (Internet of Things and Artificial Intelligence Journal, 2024)
Polynomial regression is an analytical method often used to model non-linear relationships between independent and dependent variables. This method is effective in various fields of application, such as prediction, estimation, and analysis. In this study, polynomial regression was applied to facilitate the coconut charcoal manufacturing process to predict the duration of drying time based on the measured temperature. Polynomial regression is implemented with Internet of Things (IoT) technology, where temperature data obtained from sensors is sent in real-time to a mobile application. This application provides convenience for users in monitoring and managing the coconut charcoal drying process, thereby enhancing the efficiency and quality of the final product. This integration shows excellent potential in optimizing the production process using data-driven innovative technology.